EXPLORING THE CONTRIBUTION OF MASTER’S ENGLISH LANGUAGE EDUCATION PROGRAM ON TEACHER PROFESSIONAL LEARNING - Dewi, Henda Harmantia; Triastuti, Anita (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Teacher professional learning (TPL) has been considered a significant need to strengthen teachers’ professional growth, which in turn fosters high-quality teaching and enhances students’ learning experiences. It has become a prominent interest in education around the globe, including in Indonesia. However, little is known about the contribution of a university program, especially a Master's program, towards TPL in the Indonesian context. This study aims to investigate the contribution of the Master's English Language Education (MELE) Program towards TPL on graduate students who have become teachers at once. The data were collected from graduate students of the program. A focus group was conducted with nine representatives of two classes that were categorized into two different groups. Constant comparison analysis was used as the data analysis method. The findings revealed three important themes namely applying knowledge into practice; transforming teaching through teachers’ self-inquiry; and improving knowledge, skills, and attitudes toward academic publication. The paper also presents the empirical evidence that takes place during the program and how it contributes to their professionalism.